1959
DOI: 10.1177/003072705900200503
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation of Grassland

Abstract: Grassland in the drier parts of England frequently suffers from drought in the summer months, but it is rarely irrigated and there has been little experimental evidence to show either when to irrigate or how much water to apply. Technical data on both points and on the effects of irrigation and nitrogen treatments on the yield and composition of leys are provided by the trials described here, though the practical aspects are not considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1961
1961
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Overwatering may depress yields (12,15), but this is unlikely on a free-draining soil (16). Apart from any possible loss in yield or waste arising from overwatering, practical considerations, to keep labour and equipment costs to a minimum, would require that swards should be irrigated as infrequently as possible, consistent with a worthwhile improvement in yield.…”
Section: Grassland Research Institute Hurley Berkshirementioning
confidence: 99%
See 1 more Smart Citation
“…Overwatering may depress yields (12,15), but this is unlikely on a free-draining soil (16). Apart from any possible loss in yield or waste arising from overwatering, practical considerations, to keep labour and equipment costs to a minimum, would require that swards should be irrigated as infrequently as possible, consistent with a worthwhile improvement in yield.…”
Section: Grassland Research Institute Hurley Berkshirementioning
confidence: 99%
“…This suggests that economy in both the amounts of water used and in the frequency of irrigation may be achieved by applying water only in sufficient quantities to enable the roots in the upper horizon of soil to absorb the nutrients while making further use of water from a greater depth. The work reported here investigated the efficiency of use of irrigation water, particularly when used in quantities less than that indicated by the soil water deficit INTRODUCTION Previous reports on the irrigation of grass or grass/clover swards have shown that the more frequently a sward is irrigated and the nearer to field capacity the soil is maintained the greater is the yield response to irrigation (12,13,16).…”
Section: Grassland Research Institute Hurley Berkshirementioning
confidence: 99%
“…Under dry conditions, irrigation improves the uptake and utilization of N. Usually it fails to improve response to N of mixed swards because it also enhances the contribution from clover in the control plots (4,9,14). It is perhaps not surprising that, where shortage of nitrogen limits production, white clover, which can fix nitrogen, will make a greatly increased contribution when an inadequate moisture supply is corrected.…”
Section: Some Practical Considerationsmentioning
confidence: 99%
“…Some authors (Bartels 1966;Low & Armitage 1959;Stiles 1966) have found that the clover content in mixed swards can be increased by irrigation, yet Reid & Castle (1965) found that irrigation had no significant effect on the proportion of clover, and Kleter (1968) could discover no correlation between percentage of clover in mixed swards and summer rainfall. Some authors (Bartels 1966;Low & Armitage 1959;Stiles 1966) have found that the clover content in mixed swards can be increased by irrigation, yet Reid & Castle (1965) found that irrigation had no significant effect on the proportion of clover, and Kleter (1968) could discover no correlation between percentage of clover in mixed swards and summer rainfall.…”
Section: Introductionmentioning
confidence: 99%